Phosphorylation of Vesicular Stomatitis Virus Proteins as a Possible Contributing Factor in Virion Uncoating - Witt, Donald J.; Naeve, Clayton W.; Summers, Donald F. (Journal of General Virology, 1981)
SUMMARY The relationship between the in vitro phosphorylation of vesicular stomatitis virus (VSV) proteins and virion uncoating was examined. Activation of the VSV virion kinase with low concentrations of melittin, the active peptide component of bee venom, in the presence of γ-[32P]ATP resulted in the phosphorylation of virion proteins. Following the in vitro phosphorylation of VSV proteins in the presence of melittin and deoxyadenosine triphosphate, the virion envelope was disrupted based on the accessibility of the internal ribonucleoprotein core (RNP) to the heavy metal stain, uranyl acetate, as determined by electron microscopic observation. The RNP structure was not observed in unphosphorylated virions treated with melittin and uranyl acetate. Phosphorylated virions treated with uranyl acetate subsequently lost the capacity for transcription whereas unphosphorylated virions treated with the stain retained transcriptase activity. These observations suggest that phosphorylation of VSV proteins may contribute to virion uncoating by disrupting the virus envelope.
Keywords: proteins